THE CHARGE DENSITY DISTRIBUTION AND ANTIFERROMAGNETIC PROPERTIES OF AZURITE CU3[CO3]2(OH)2 - Belokoneva E.L.; Gubina Y.K.; Forsyth J.B. (My University, 2001)
The structure and bonding in azurite are investigated on the basis of accurate single-crystal X-ray diffraction data. Both spherical IAM and pseudoatom models have been used in the refinements. The deformation electron density: dynamic (IAM) and static (pseudoatom) are mapped for the CO3 group and for Cu(1) and Cu(2) squares in different sections. The carbonate group in azurite, not constrained to have trigonal symmetry, exhibits peaks in both static and dynamic maps which result from σ-bonds between C–sp2 hybrid orbitals and O–p orbitals with some delocalisation of density in the dynamic map because of the thermal motion of oxygens. For the analysis of crystal fields and for the multipole calculations, coordinate systems on the Cu-atoms have been chosen as for a Jahn-Teller octahedron, but with the normal to the square as the z-axis instead of the absent apical oxygens. In both Cu squares there are peaks which result from single Cu–O σ-bonds. Most remarkable is the preferential occupation of the non-bonding 3d orbitals of Cu-atoms being above and below the Cu-squares. The centre of these peaks for the Cu(1)-atom makes an angle with the c-axis ∼53° in the ac plane. This direction corresponds to the maximum magnetic susceptibility at ambient temperature. The real atomic charges of Cu-atoms in azurite determined from multipoles are close to Cu+1. The occupancies of the 3d atomic orbitals show that non-bonding orbitals in both Cu-atoms are most populated, in contrast to bonding orbitals, as is typical for the Jahn-Teller octahedron. The absence of apical oxygens makes this effect even more pronounced. It is suggested that the antiferromagnetic structure below 1.4 K will be collinear and commensurate with b′=2b.
Keywords: Azurite; experimental charge density; orbital occupation; antiferromagnetic properties